2021
DOI: 10.3389/fphar.2021.586788
|View full text |Cite|
|
Sign up to set email alerts
|

Xiaoyaosan Alleviates Hippocampal Glutamate-Induced Toxicity in the CUMS Rats via NR2B and PI3K/Akt Signaling Pathway

Abstract: Purpose: It is revealed that Xiaoyaosan could reduce glutamate level in the hippocampus of depressed rats, whose metabolism leads to the pathophysiology of depression. However, the underlying mechanism remains unclear. This study aims to explore the effect of Xiaoyaosan on glutamate metabolism, and how to regulate the excitatory injury caused by glutamate.Methods: Rats were induced by chronic unpredictable mild stress, then divided into control, vehicle (distilled water), Xiaoyaosan, fluoxetine, vehicle (DMSO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Homer1b/c, mGluR5, p-mTOR, mTOR, p70S6 kinase, p-p70S6 kinase, p-4E-BP1, 4E-BP1, PSD-95 and SYP expressions in hippocampal CA1 region of experimental rats were detected by Western blot analysis according to the protocol [ 6 ]. Details are listed at Additional file 1 : Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homer1b/c, mGluR5, p-mTOR, mTOR, p70S6 kinase, p-p70S6 kinase, p-4E-BP1, 4E-BP1, PSD-95 and SYP expressions in hippocampal CA1 region of experimental rats were detected by Western blot analysis according to the protocol [ 6 ]. Details are listed at Additional file 1 : Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…or Bupleurum scorzonerifolium Willd. , is a common component of Chinese herbal prescriptions such as Xiaoyaosan [ 6 ] and Chaihu-Shugan-San [ 7 ], which are administered clinically to improve symptoms of depression . Saikosaponin D (SSD) is a pharmacologically active ingredient extracted from Radix Bupleuri [ 8 , 9 ], which is capable of ‘dispersing stagnated liver qi for relieving qi stagnation’ according to traditional Chinese Medicine (TCM) theory.…”
Section: Introductionmentioning
confidence: 99%
“…CUMS, acknowledged as a putative animal model of depressive-like behavior and an imitation of life stress, is reliable and stable ( Willner 1997 ; Mineur et al, 2006 ). Lack of pleasure is an essential manifestation of depression, and SPT is the gold standard for evaluating the degree of pleasure deficiency in depressed animals ( Weiss 1997 ; Zhou et al, 2021 ). In this study, compared with rats in unstressed group, CUMS rats showed a lower degree of preference for sucrose after 4 weeks of CUMS treatment, which increased the sucrose preference index and demonstrated an antidepressant-like effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, the CUMS-exposed group was then divided into five groups: model, FH (1.8 mg/kg), TTWC-L (low), TTWC-M (middle), and TTWC-H (high) dose groups (60, 120, 240 mg/kg), with eight rats in each group. The dose of FH was converted from the clinical dose of 20 mg/d ( Zhou et al, 2021 ). The unstressed and vehicle treated CUMS groups were administered saline every day, while the other groups received intragastric administration of the corresponding drugs for 2 weeks.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The classic Chinese formula Xiaoyaosan, originated from the book Prescriptions of the Bureau of Taiping People's Welfare Pharmacy in Song Dynasty of China, is one of the effective traditional Chinese compound recipes in treating psychoemotional related symptoms and diseases (Zhang et al, 2019). According to the recent clinical and basic studies, Xiaoyaosan has a multi-target regulating effect which is reflected in the treatment of depression-related diseases (Li et al, 2015;Jiao et al, 2019;Xiong et al, 2019;Liu et al, 2020;Zhou et al, 2021). In the pathogenesis study of depression, it is found that psychological and physical stressors can activate the immune system, lead to inflammation, and then participate in the development of depression (Iwata et al, 2013).…”
Section: Introductionmentioning
confidence: 99%